Security and Privacy in the Digital Era: Overcoming Challenges and Enhancing Protection - I Wayan Sindia Griya Danika (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2023)
The advancing information technology has provided users in the digital era with faster and easier access to information. However, this progress also brings forth new challenges in terms of information security and privacy. Cybercrime, hacking, and identity theft are some of the threats that need to be addressed in order to uphold the security and privacy of information. This article discusses the challenges and threats in information security and privacy in the digital era and provides strategies for enhancing protection. The strategies discussed include the implementation of data encryption, the use of strong passwords, and stringent data access management. Additionally, it is important for users and organizations to understand these risks and threats and take action to safeguard their information security and privacy. By following the guidelines and strategies outlined in this article, it is hoped that users and organizations can remain safe and protected in their use of information technology. Furthermore, awareness and appropriate actions can also help improve overall information security and privacy in the digital era.